2017
DOI: 10.1002/mrm.26819
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated three‐dimensional multispectral MRI with robust principal component analysis for separation of on‐ and off‐resonance signals

Abstract: Three-dimensional multispectral imaging can be highly accelerated by varying undersampling between bins and separating on- and off-resonance. Magn Reson Med 79:1495-1505, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Among various BSS algorithms, robust principal component analysis (rPCA) has been introduced for separation of background signal This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ in dynamic MRI [14], on/off-resonance signal representation in multispectral imaging [15] and elimination of MR artifacts [16], [17]. Based on singular value decomposition (SVD) analysis, rPCA extracts redundant signal sources using low-rank property (or fixed-rank property) and encourages the sparsity of the residual signal.…”
Section: Introductionmentioning
confidence: 99%
“…Among various BSS algorithms, robust principal component analysis (rPCA) has been introduced for separation of background signal This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ in dynamic MRI [14], on/off-resonance signal representation in multispectral imaging [15] and elimination of MR artifacts [16], [17]. Based on singular value decomposition (SVD) analysis, rPCA extracts redundant signal sources using low-rank property (or fixed-rank property) and encourages the sparsity of the residual signal.…”
Section: Introductionmentioning
confidence: 99%
“…Partial Fourier reconstruction methods can be used to fill in the missing phase‐encoding lines after the shot‐LLR reconstruction by using the conjugate symmetric property of the k‐space. Similar to the idea of virtual conjugate coils, which is an alternative way of exploiting this property, we generate virtual conjugate shots (VCSs) by flipping and conjugating the acquired data, and treating them as additional shots to avoid the estimation of the low‐resolution phase from the central k‐space data. The decomposition of the LLR matrices with VCS is provided in the Appendix.…”
Section: Theorymentioning
confidence: 99%
“…The strength of the differentiation varies according to TSL, and it may be better to use different thresholds for the images at different TSLs. In previous studies (20,32), L+S decomposition was applied to dynamic imaging or multispectral imaging, in which the data did not fit a low-rank only component and therefore the sparse component contains significant energy. L+S decomposition was applied in static imaging in this study, but we found that some image details can still be observed in the sparse component, especially in the cartilage region.…”
mentioning
confidence: 99%